Liquidity and Manipulation of Executive Compensation Schemes - Axelson, Ulf; Baliga, Sandeep (Review of Financial Studies, 2009)
Compensation contracts have been criticized for encouraging managers to manipulate information. This includes bonus schemes that encourage earnings smoothing, and option packages that allow managers to cash out early when the firm is overvalued. We show that the intransparency induced by these contract features is critical for giving long-term incentives. Lack of transparency makes it harder for the owner to engage in ex post optimal but ex ante inefficient liquidity provision to the manager. For the same reason, it is often optimal to “pay for luck ” (i.e., tie long-term compensation to variables that the manager has no influence over, but may have private information about, such as future profitability of the whole industry). (JEL G34, J33) How can effective executive compensation be set up when managers can manipulate short-term information? Although it is a long-standing question in corporate governance, public focus on this issue reached new heights at the beginning of the millennium after governance scandals at Enron and WorldCom and many other corporations. A common thread in these scandals was that accounting manipulation was used to increase stock prices. In a number of cases,